Technology, innovation and SMEs' export intensity: Evidence from Morocco - Paul Jones (Technological Forecasting and Social Change, 2023)
This study seeks to understand the scarcely examined relationships between SMEs' foreign technology licensing, R&D expenditure, innovation and export intensity. Espousing an integrated open innovation and self-selection paradigm, observations of 446 Moroccan SMEs are analysed through structural equation modelling. The definitive path analysis showed that foreign technology licensing and R&D expenditure distinctively affect innovation and, in turn, innovation increases export intensity. In further insights, to illustrate how the distribution of these inputs enhances internationalisation, a probabilistic analysis shows that foreign technology licensing, R&D expenditure and innovation will incrementally stimulate export intensity by >71 %. The permutations of these variables in the fresh setting of Morocco summon scholars' empirical attention at the same time as policymakers' consideration.